Analisis Kadar Metabolit Sekunder, Histokimia, dan Aktivitas Antioksidan Akar Acalypha indica L. - Novia Agustina; Nurul Istiqomah (Journal Syifa Sciences and Clinical Research, 2021)
Acalypha indica L. is a species of wild plant that has secondary metabolites are used as medicine, but the usage is not optimized yet. The objective of of this study was to determine secondary metabolites content, location and distribution of secondary metabolites, and also the capacity for antioxidant. Secondary metabolites content was determined included phenol, flavonoids, tannin of chloroform and methanol extracts from Acalypha indica L. root, using spectrophotometre. Histochemical test was done by making fresh sliced preparation which was reacted with reagent. Antioxidant activity was determined by using DPPH method. The result of this study showed that secondary metabolites content of chloroform extract, were phenol 9,89 ± 0,77 %GAE, flavonoids 5,87 ± 1,40 %QE, and tannin 3,33 ± 1,21 %GAE, while methanol extract were phenol 45,11 ± 4,86 %GAE, flavonoids 19,87 ± 0,61 %QE, and tannin 6,76 ± 0,31 %GAE. Histochemical test showed that phenol, flavonoids, tannin, and alkaloids were found in Acalypha indica L. root. Antioxidant activity showed the IC50 value was 161,81 ± 7,88 μg/mL for chloroform extract and 92,81 ± 4,33 μg/mL for methanol extract.